The Haemato-biochemical Alteration in Bacteria Associated Respiratory Tract Infection in Dog - Sarkar, Bratati Deb; Barman, Ditul; Kumar Nath, Mrinal; Ghosh, Tanay; Hazorika, Mousumi; Kachari, Jodumoni; Srikanth, Sreeramdas (International Journal of Bio-resource and Stress Management, 2024)
The research was undertaken during October, 2022 to June, 2023 to study the changes in haemato-biochemical values of the dogs suffered from respiratory tract infection due to bacteria. Blood samples were collected from healthy control group (Group A) and each dog of different treatment groups (Group B, Group C and Group D) on the 0th day (pre-treatment) and the 10th day (post-treatment) in K3-EDTA vacutainer tubes as well as clot activator-coated vacutainer tubes for haemato-biochemical estimation. In the result of haemato-biochemical study the highly significant difference (**p<0.01) was found in total leucocyte count, absolute neutrophil count and C-reactive protein. Statistically no significant difference (p>0.05) was observed in total erythrocyte count, haemoglobin, absolute eosinophil count, absolute lymphocyte count and albumin. In case of total protein a highly significant difference (**p<0.01) was observed between Group A and Group B on day 0 and on day 10. A highly significant difference was also observed between (**p<0.01) Group B and Group C; Group B and Group D on day 0 and day 10. On the other hand no significant difference (p>0.05) was observed within treatment groups. In case of globulin, statistically no significant difference (p>0.05) was obtained between the Group A and all the treatment groups on day 0 and day 10. No significant difference (p>0.05) was observed within treatment groups. However, a significant difference (**p<0.01) was found between Group B and Group C; Group B and Group D on 0th day and on the 10th day.